COMPETITIVE PROFILE MATRIX SEBAGAI ALAT ANALISIS STRATEGI PEMASARAN PRODUK ATAU JASA - MOHD. HARISUDIN (Universitas Sebelas Maret, 2011)
Simple understanding of the strategy is a tool to achieve the goal, but in formulating a good strategy requires a mechanism that is not simple. This mechanism is not easy to do small and medium entrepreneurs. Competitive Profile Matrix is one alternative to overcome these business, because in the Competitive Profile Matrix is known in real comparison between products or services offered to consumers than competitors' products or services. While alternative strategies can formulate based on the value of weighted factor. Selection is done by QSPM chosen strategy.